Esophageal foreign bodies: review of 84 cases - Flórez Sarmiento, Cristian (2023)
The presence of esophageal foreign body (EFB) is a common emergency in gastroenterology. The protocol for management and endoscopic intervention can be variable among institutions. Objective: To define the clinical characteristics of EFB in adults, its radiological and endoscopic diagnosis, and complications based on a sample of patients in a gastroenterology center. Materials and methods: Case series of patients admitted from the emergency department and referred to the gastroenterology department with a presumptive diagnosis of EFB. Clinical variables were collected, as well as characteristics, comorbidities, time of evolution and diagnostic opportunity, confirmatory studies, and complications. Results: 84 subjects, 70% men, mean age 45 (range: 17-87; SD 12.5) years. Urgent upper endoscopy was performed in 98.8% of the patients, with an average in-hospital stay of 2.5 days. 93% had no associated underlying pathology, in 6/84 (7.14%) patients structural or functional esophageal pathology was documented. 59/84 (70.2%) patients consulted in the first 24 hours, in 57.6% the presence of foreign body was confirmed endoscopically. In 67/84 (79.76%) patients radiography was performed prior to endoscopy, of which 62/67 (92.5%) had an abnormal result. Seventy percent of confirmed EFB were fish bones. The most frequent site of localization was in the cricopharyngeal region in 90% of the cases. In 66/84 (78.6%) subjects there was absence of complications, followed by deep laceration in 10/84 (11.9%) cases. In 3/84 (3.6%) cases complications requiring surgery were identified. Conclusions: Endoscopic intervention in the first 24 hours is an opportune moment to identify complications and provide the indicated treatment.